The Effectiveness of Onion Extract Allium sativum to Prevent Koi Herpesvirus (KHV) Infection on Common Carp Cyprinus carpio - Sri Nuryati; P. Giri; Y. Hadiroseyani (Jurnal Akuakultur Indonesia)
Common carp is one of consumption fish that has delicious meat, high pritein level, and easy in farming. The serious problem in common carp farming is koi herpesvirus infection.  Onion extract potency to improve immune system was estimated to prevent disease infection.  The testing of the garlic extract through food could be used as efforts to increase endurance of common carp fish Cyprinus carpio to koi herpesvirus infection that was considered from blood parameter. Fish that was used was measuring 9-11 cm with the treatment of food containing  30, 50, and 70 gr/100 ml onion extract. Fish was acclimated for seven days  in 60×30×30 cm3 aquarium before used. Garlic extract diet in food gave increasing of fish immune system that was infected by koi herpesvirus. The increased of leucocytes of blood fish with onion extract diet was faster than possitive control. The dose of B treatment (50 gr/100 ml) was the best dose gave short incubation periode comparing other treatment. Survival rate (SR) of this B treatment was highest, i.e. 91.7%, while survival rate of negative control was 50%.